Zróżnicowanie roślinności gospodarczych borów sosnowych na tle typów siedliskowych lasu w Nadleśnictwie Turawa - Stefańska-Krzaczek, Ewa; Pech, Paweł (Leśne Prace Badawcze, 2014)
The utility of phytocenotic indices in the diagnosis and classification of forest sites might be limited because of vegetation degeneration in managed forests. However, even in secondary communities it may be possible to determine indicator species, although these may differ from typical and well known plant indicators. The aim of this work was to assess the vegetation diversity of Scots pine stands in representative forest site types along a moisture and fertility gradient. In total 120 sample plots from Turawa forests were included in the study. These plots represented young (21–40 years) and old (> 80 years) Scots-pine-dominated stands. The forest sites were categorized according to Polish site classification. Four site categories were studied: Bśw (very nutrient-poor and mesic sites), BMśw (nutrient-poor and mesic sites), BMw (nutrient-poor and moist sites), LMw (quite nutrient-rich and moist sites). The species composition of the forest patches studied hardly differed among forest site types. Almost all of the vegetation in site Bśw was different from both moist site types (BMw and LMw). Sites Bśw and LMw had the exclusive species determined as site indicators. Moreover, young stands had their own site type indicator species which differed from old stands. Numerical classification showed that only two plant communities were widespread: Leucobryo-Pinetum in Bśw and BMśw, and the community of Pinus sylvestris and Molinia caerulea in BMśw, BMw, LMw. In secondary communities typical indicator species may not be useful, but it is possible to determinate species that are locally unique to forest site type. Despite the convergence in the composition of the plant community resulting from tree stand unification, plant communities have the capacity for a more diverse composition. Tree stand conversion can increase phytocenotic diversity.